Modeling and Simulation of 115.2 kWp Grid-Connected Solar PV System using PVSYST - Bhattarai, Nawraj (Kathford Journal of Engineering and Management, 2018)
The renewable sources such as solar, wind, biomass, etc. are often used for electricity generation for their availability, no green-house gas emission and solar photovoltaic is major among them. Many On-Grid PV systems are being installed around the globe nowadays to reduce electricity dependency on a single source and thus enhance availability of energy sources. Kathmandu, Nepal receives sufficient sunshine with insolation around 4.5 to 5 kWh/m2/day, which justifies essence of grid-connected solar PV installations. A 115.2 kWp solar plant has been installed at Tribhuvan University Teaching Hospital (TUTH), Maharajgunj, Kathmandu to fulfill its own load demands and reduce the electricity bill of the building. The generated energy is not fed to the grid currently. The detailed On-Grid solar PV system is modeled, and performance parameters such as Performance Ratio, Specific Yield and Capacity Utilization Factor as defined by International Electro technical Commission are estimated using simulation techniques from PVSYST. The actual generation of the existing system within one year of installation is measured to be 35 MWh but simulation tool suggests that total 199 MWh can be generated using similar capacity panel, with system being totally on-grid type. Using PVSYST, the performance parameters are found to be performance ratio 83.5 % and Specific Yield 1728 kWh/kWp respectively. Thus, this paper intends to calculate performance parameters of existing system as well as performance of identical sized, totally on-grid system, simulated using PVSYST.